Training patterns of wheelchair basketball players in Turkey - (:unkn) unknown (My University, 2008)
The aim of this study was to analyze technical drills, warm-up and cool-down exercises used by wheelchair basketball players of the Turkish league in relation to training sessions. 33 male wheelchair basketball players participated in the study (mean age 26.6±5,95 years). All players reported that they used warm-up exercises before the training, but only 20% used cool-down exercises after the training session. 60,6% of the participants trained 3-5 hours in a week, while 87,9% trained at 2 days of a week. None of the players used special equipment for improvement of flexibility, strength and endurance. Some players and teams reported that they had technical-tactical drills in the training. Generally the training consisted of a short warm-up and technique drills followed by a match. In conclusion, training intensity, technical-tactic drills and conditioning exercises in the training session of the players in the Turkish wheelchair leagues did not met the relevant recommendations.